Formation of Waste Care Cadres Through A Community-Based Waste Bank Institution - Luthfi, Asma; Wijaya, Atika; Rohmi, Maulidtha Kholifatur; Paramita, Yuni; Fajar, Muhammad Hayyun (Jurnal Abdimas, 2023)
Rubbish Still become problem crucial that must be handled. Production increasing rubbish day the more increase make Power accommodate landfill (Place Final Disposal) waste Already exceed its capacity. For that, then management rubbish No Again only become not quite enough answer government, but it is also necessary awareness and effort real public in deal with it. Problems found is Still lack of management rubbish based organized community with OK, wrong attempt to get it done with partner is increase participation public in management rubbish in a way independent through formation cadre care trash that will become Waste Bank Manager at RT 04 RW 05 Subdistrict Mangunsari Subdistrict Gunungpati, Semarang City. Suite activity done start from stage preparation, stage implementation, and stages evaluation. From activities devotion This obtained results ie growing awareness and participation active partner in manage rubbish in a way independent, increasing knowledge and skills partner in managing waste banks, as well realization readiness partner in establishing a waste bank in its area.